The Position Of The Right To Residence Of The Indigenous People Of Torsiaje Is Seen From Article 18B Of The 1945 Constitution - Siti Zahra Karina Jusdin (Estudiante Law Journal, 2019)
: This study aims to find out the position of the right to residence of indigenous peoples torsiaje seen from article 18b of the 1945 Constitution. The methods used in this research are empirical normative research and use a legal approach or statute approach and use case approaches as well as data analysis techniques using qualitative approach analysis. The results of this study show that the Position of Rights to The Residence of Indigenous Peoples torsiaje Seen From Article 18b of the 1945 Constitution states that everyone has the right to live a prosperous life born and inward, residing, and getting a good and healthy living environment. In reality, not all communities can enjoy decent housing. This is due to differences in growth and regional development and the small government's attention to low-income communities. So that the state must immediately provide legal protection and guarantees for people who do not have or even want to move home to a more viable place by making agreements and discussions with relevant community groups.  The government must be able to accelerate the making of village regulations in which it contains substance related to the division of housing rights for the community and encapsidation to create clarity in doing everything in the community.